Effect of hydrodynamic interaction on free volume changes and the mechanical properties of SGFR‐PBT composites. Issue 6 (8th July 2016) - Munirathnamma, L.M.; Ravikumar, H.B.
Abstract : In order to explore the effect of short glass fiber reinforcement (SGFR) on the mechanical properties of polybutylene terephthalate (PBT), 10–40 wt% of short glass fibers (SGF) are reinforced into PBT matrix. Microstructural characterization has been performed by positron lifetime technique. The fractional free volume obtained experimentally show negative deviation at 20, 30, and 40 wt% of SGF from the linear additivity relation. This indicates the improved adhesion between the short glass fiber and PBT matrix at 20, 30, and 40 wt% of SGF. The evaluated hydrodynamic interaction parameter ( h ) suggests the generation of excess friction at the interface of SGFR‐PBT composites. The positron lifetime parameters of SGFR‐PBT composites are correlated with the mechanical properties viz., tensile strength (TS), Young's modulus (YM), and elongation at break (EB). The decrease of crystallinity and average crystallite size of SGFR‐PBT composites evaluated by X‐ray diffraction results indicate the induced chemical interaction between PBT side chain and SGF due to the silane treatment of E‐glass fibers. The decreased positron lifetime parameters, reduced crystallinity, and crystallite size and improved mechanical properties are attributed to the improved chemical and physical interaction between the functional groups of SGF and PBT matrix. This is also evident from Fourier transform infrared spectrometry (FTIR) studies. POLYM. COMPOS., 39:1878–1886, 2018. © 2016 Society of Plastics Engineers